Retinoid activation of retinoic acid receptors but not of retinoid X receptors promotes cellular differentiation and replication of human cytomegalovirus in embryonal cells. - Angulo, A (1995)
The susceptibility of human embryonal cell line NT-2/D1 to replicate human cytomegalovirus (hCMV) is dependent on retinoic acid (RA) stimulation. Physiological responses to retinoic acid involve two distinct subfamilies of nuclear receptors, the RA receptors (RARs) and retinoid X receptors (RXRs), which function by activating transcription as heterodimeric or RXR homodimeric complexes from cis-acting DNA response elements. At present, it is not clear whether the association between these two classes of receptors can lead to multiple distinct induction pathways by signalling one or both receptor partners. Here we have determined, by selectively activating endogenous receptors with novel synthetic ligands specific for either RARs or RXRs, what ligand interaction is physiological in the retinoid receptor pathways necessary for inducing replication of hCMV in differentiated embryonal cells. We show that ligand binding to RAR alone is sufficient and that exclusive ligand activation of RXR is insufficient for inducing replication of hCMV. We also find that differentiation and inhibition of NT-2/D1 cell growth are promoted by compounds that signal the RAR pathway. These results provide direct evidence that RAR ligand-mediated physiological responses are separable and distinct from RXR ligand activation functions. Moreover, our results provide insight into a hormone response pathway for cellular differentiation that might be coopted by hCMV in the host.